PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PEGADAIAN CABANG PEKANBARU - ", Rahmawati; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to analyze the effect of organizational culture on organizatonal commitment with job satisfaction as intervening variable for employees of PT. Pegadaian Cabang Pekanbaru. The metode used is descriptive and quantitative using the program SPSS 23. The Population in this study were all employees at PT. Pegadaian Cabang Pekanbaru 156 employees. The sample used was 61 employess. The sampling technique used in this study is proportional stratified random sampling anda methodes of collecting data through questionnaires and interviews. The data analysis technique uses simple linear regression and multiple linear regression. The results of the analysis used the validity test, realibility test, regression test, determination test,, t test and f test. So it can be conclude that organizational culture has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational commitment, organizational culture has a positive effect and significant on organizational commitment and organizational culture has an indirect effect on organizational commitment with job satisfaction as an interevning varible employee of PT. Pegadaian Cabang Pekanbaru. Keyword : Organizational Culture, Job Satisfaction, Organizational Commitment